Metaphysical Sufism of al-Durr al-Nafīs: Between Controversy of the Scholars and Interest of the Public - Mujiburrahman Mujiburrahman (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2022)
This article discusses the controversy on the Sufi metaphysics contained in a treatise called al-Durr al-Nafīs written by Muhammad Nafis al-Banjari, and the interest of the public in it. This study analyses a number of studies of this treatise, and it is enriched by interviews with some relevant Islamic scholars. Some Islamic scholars reject the Sufi doctrines of Muhammad Nafis on the ground that they are not in line with Islamic orthodox teachings. There are some Islamic scholars who simply say that the doctrines of the treatise are not included in the Ahl al-Sunnah camp, while others say that they are misguided and misleading. On the other hand, there are some Islamic scholars who say that the doctrines are actually orthodox, but they are only for intellectually and spiritually gifted people. Although most of the scholars suggest that the treatise should not be freely taught to, or circulated among, common people, thanks to print technology and the rise of interest in Sufism, this treatise has been more widely read in religious gatherings and circulated not only in different parts of Indonesia but also in Southeast Asia.